Facile preparation of UiO-66 /PAM monoliths via CO2-in-water HIPEs and their applications. Issue 56 (19th September 2018) - Dong, Yong; Cao, Liqin; Li, Jing; Yang, Yongxia; Wang, Jide
Abstract : A novel UiO-66/PAM composite monolith with high performance was synthesized through a HIPE template. Abstract : A novel clean method to synthesis a composite monolith was developed. Given its amphiphilic property, UiO-66 can emulsify water and CO2 to format a high internal phase emulsion (HIPE) under certain conditions. These UiO-66-emulsified Pickering HIPEs can be used as templates to prepare interconnected macroporous MOF/polymer composite monoliths. The effects of UiO-66 amount, cross-linking agent concentration, and CO2 –water ratio on UiO-66/PAM structures were investigated. Then, the as-synthesized MOF/PAM composites were characterized by TGA, XRD, SEM, and FT-IR analyses, as well as rheological and DMA measurements. The results indicated that the composites are interconnected with hierarchical pores, and the diameter of the voids is 10–50 μm. The directly prepared monoliths exhibited relatively high stresses at 82% strain and recovered their shape quickly. The adsorption capacity of the composites for methylene blue (MB) is 50 mg g −1 at a faster adsorption rate. The monoliths also exhibit underlying applications in edible oil–water separation.